2017
DOI: 10.1371/journal.pbio.2000936
|View full text |Cite
|
Sign up to set email alerts
|

CACNA1C gene regulates behavioral strategies in operant rule learning

Abstract: Behavioral experiments are usually designed to tap into a specific cognitive function, but animals may solve a given task through a variety of different and individual behavioral strategies, some of them not foreseen by the experimenter. Animal learning may therefore be seen more as the process of selecting among, and adapting, potential behavioral policies, rather than mere strengthening of associative links. Calcium influx through high-voltage-gated Ca2+ channels is central to synaptic plasticity, and altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Acetazolamide could abolish stress-induced ataxia in mice [ 144 ] Apoptotic pathway in ataxia [ 152 ] CACNA1C Calcium voltage-gated channel subunit alpha1 C Cav1.2 L-type Genetic Cacna1c rat model [ 239 ]. Cacna1c knockout model [ 240 ]. Mouse line with an inactivation of the Cav1.2 gene in the hippocampus and neocortex (Cav1.2 (HCKO)) [ 241 ].…”
Section: Resultsmentioning
confidence: 99%
“…Acetazolamide could abolish stress-induced ataxia in mice [ 144 ] Apoptotic pathway in ataxia [ 152 ] CACNA1C Calcium voltage-gated channel subunit alpha1 C Cav1.2 L-type Genetic Cacna1c rat model [ 239 ]. Cacna1c knockout model [ 240 ]. Mouse line with an inactivation of the Cav1.2 gene in the hippocampus and neocortex (Cav1.2 (HCKO)) [ 241 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Q-PH models, the value of choosing an action a at state s is parametrized by the variable Q s,a . The Pearce–Hall update mechanism generalizes the classic Rescorla–Wagner rule by introducing an associability variable a , which tracks the uncertainty of the animal on the trial outcome and is proportional to its attention to CS 34 , 36 , 72 , 73 . The associability affects the action value Q s,a as a feedback-dependent dynamical learning rate.…”
Section: Methodsmentioning
confidence: 99%
“…Cacna1c knockout mice did not show an overall behavioral deficit; however, detailed behavioral analysis showed that these animals gained reward based on an outcome-based strategy, rather than learning cue–reward associations, basing their responses more on the previous location of the reward. 55 Similarly, Temme et al 54 found that mice lacking forebrain Cacna1c could learn contextual and spatial associations normally but were impaired on more subtle tests of context discrimination and pattern completion. A recent study also demonstrated impacts of Cacna1c hemizygosity on social behavior and communication.…”
Section: Discussionmentioning
confidence: 97%
“…Our results are broadly consistent with previous studies on mice with forebrain-specific total knockout of Cacna1c . 54,55 Koppe et al 55 found forebrain-specific conditional Cacna1c knockout mice adopt different behavioral strategies during an operant reward-based learning task compared to controls. Cacna1c knockout mice did not show an overall behavioral deficit; however, detailed behavioral analysis showed that these animals gained reward based on an outcome-based strategy, rather than learning cue–reward associations, basing their responses more on the previous location of the reward.…”
Section: Discussionmentioning
confidence: 99%